A circular home; investigating tools for resilient architecture - Richardson, Sandra (My University, 2024)
Our society has urgent challenges with water supply, food production and electricity availability, due to environmental issues and wars. Architects can contribute more conscious to all these fields by letting our architectural tools be based on nature’s resources and its conditions. By considering one of the main tasks of architecture, keeping us warm, already in the sketch phase the buildings get less dependent on mechanical systems, and by seeing water and food more as circular systems our architecture becomes more resilient. To get background knowledge, literature and built references was studied. The knowledge was then translated to design strategies, to act as a toolbox in the design phase. As a complement to the design strategies, references have been studied and a building program was created, that also inspires and imposes demands on the building. The result is a prototype house for one family, which in this case was tested on a plot outside Gothenburg. A detailed sun study was carried out for the site as it impacts several design principles. In the proposal, rooms are placed according to the time of day they are used and temperature requirements for each room in relation to the sun movement. The common spaces are allowed to expand and shrink while need and season changes, further the user can experience different zones within the home, ranging from colder rooms to different greenhouse zones, thus blurring the boundaries between outside and inside. The house is designed with solid materials such as wood and brick, and through its thoughtful placement, they contribute to the heating of the house as well as the architectural expression. The tricky part is to do precalculation of how it impacts the indoor climate when trusting nature. If there were more time, an investigation of putting several units together would have been interesting. The tools can be implemented on a larger scale than a singlefamily house, thus contribute to a more sustainable construction sector with resilient architecture
Keywords: Climatic architecture, design tools, crisis preparedness